SEKOLAH PENERBANG MAGUWO: Pembentukan dan Peranannya pada masa Revolusi Fisik (1945-1950) - Ikmal Maulana; Erlina Wiyanarti (Universitas Pendidikan Indonesia dan APPS (Asosiasi Pendidik dan Peneliti Sejarah), 2018)
The background of the research is examine the topic on how the military’s education system in the early days of independence is relatively less researched compared to research on figures, strategies or battles during the independence revolution. The main issue raised in this undergraduate thesis is “how was the process of formation and the role of the Maguwo’s Aviation School in 1945-1950?”. In the process to answer that main issue, the author used the historical method to perform four steps namely heuristics, critics of sources, interpretation and historiography. To facilitate the analysis, the author used the interdisciplinary approach through studies in the field of education and sociology by using the vocational education’s concept and the role’s concept. Based on the results of the research it can be found that first, the formation’s background of the Maguwo’s Aviation School was the absence of aviation education’s institutions that could fulfill the needs of the aviators in order to defended the independence from the Dutch’s threat. Second, the absence of the aviation educational institutions, Adisutjipto took the initiative to setted up an aviation school in Maguwo and became the instructor at the school. Third, the curriculum undertaken at the Maguwo’s Aviation School is “Cakap Terbang” means that the training undertaken at this school is directed the cadets to have the skill in flying the plane quickly. Fourth, although the facilities and infrastructure which supported the implementation of education was limited, but because of the unyielding’s spirit, the cadets were able to demonstrate the successful implementation of the education, one of them was the success of the cadets in executed operations against the Dutch’s position in Semarang, Salatiga and Ambarawa. But, the aviation history is a history of sacrifice because there were also cadets and school instructors who died while executed the air operations as experienced by Adisutjipto, Abdulrachman Saleh and Adi Sumarmo who died in the Dacota VT-CLA.